Zinc oxide scaffolds on MgO nanocubes - Stankic, Slavica; Sternig, Andreas; Finocchi, Fabio; Bernardi, Johannes; Diwald, Oliver (Nanotechnology, 2010)
Powders of isolated and well-dispersed oxide nanocubes are promising components for photoelectronic applications that benefit from tunable optical properties, surface reactivity and the ease of realization of their controlled assembly. Here, we demonstrate that combustion of zinc and magnesium metal vapors at reduced pressures followed by subsequent vacuum annealing of the resulting nanoparticle powders yields single-crystalline ZnxMg1 - xO nanocubes of exceptional regular cubic shape and edge lengths below 25 nm. In line with ab initio calculations, which predict preferential Zn2 + segregation into low coordinated surface elements of the MgO nanocubes, we track the occupation of edge sites by chains of Zn2 + –O2 - units through their spectroscopic signatures. As a method to generate composite nanostructures with controlled spatial distribution of the chemical components, the annealing induced ion segregation can be extended to other well-dispersed metastable nanoparticles. We expect that the energy of segregation mainly depends on the site coordination number, which can promote controlled demixing within the nanoparticles
EAM Import::2019-03-12